2019
DOI: 10.4103/ijem.ijem_116_19
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D toxicity: A prospective study from a tertiary care centre in Kashmir Valley

Abstract: Background: Vitamin D toxicity (VDT), a “not uncommon” cause of hypercalcemia, can be life-threatening and cause substantial morbidity, if not treated promptly. Aims: To describe presentation, management, and outcome in 32 patients with VDT diagnosed over 3 years. Materials and Methods: Patients presenting with VDT at a tertiary care centre in Srinagar Kashmir India were included. Evaluation included detailed history and biochemical tests inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 13 publications
0
18
0
2
Order By: Relevance
“…Treatment with 2000 to 5000 IU of vitamin D3 daily has not been associated with vitamin D toxicity, 31,32 whilst super high doses for prolonged periods have been reported to cause hypercalcemia and nephrolithiasis. [33][34][35] In our population of healthy vitamin D deficient adolescents, we empirically treated the vitamin D deficient subjects with 2000 IU of vitamin D3 daily for 3 months. Following treatment with vitamin D3, there was a 56.02% increase of the mean vitamin D levels from the mean pretreatment values and the levels normalized in 80.39% of the subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with 2000 to 5000 IU of vitamin D3 daily has not been associated with vitamin D toxicity, 31,32 whilst super high doses for prolonged periods have been reported to cause hypercalcemia and nephrolithiasis. [33][34][35] In our population of healthy vitamin D deficient adolescents, we empirically treated the vitamin D deficient subjects with 2000 IU of vitamin D3 daily for 3 months. Following treatment with vitamin D3, there was a 56.02% increase of the mean vitamin D levels from the mean pretreatment values and the levels normalized in 80.39% of the subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In adolescence, plasma levels decrease and needs increase; however, the recommendation is the same as for adults. [ 17 ]…”
Section: Methodsmentioning
confidence: 99%
“…[ 18 ] On the other hand, the doses that have been documented to lead to toxicity are above 40,000 IU to 50,000 IU per day. [ 16 , 17 ] This is considered as potentially severe condition whose symptoms are associated to secondary hypercalcemia and are mainly of a gastrointestinal nature (anorexia, nausea, vomit, constipation, diarrhea, abdominal pain) and polydipsia, polyuria, muscular weakness and fatigue, among the most relevant. [ 19 ]…”
Section: Methodsmentioning
confidence: 99%
“…Vitamin D3 supplementation is commonly used for musculoskeletal health, and there has been an increase in use as studies report health benefits including improvement in symptoms of depression and blood pressure, and decreased respiratory infections and mortality [ 1 , 2 ]. Although hypervitaminosis D is uncommon, multiple studies have demonstrated toxicity from high dose supplementation [ 3 , 4 , 5 , 6 , 7 , 8 ]. Hypervitaminosis D results in hypercalcemia and classically presents with hyperphosphatemia [ 9 ].…”
Section: Introductionmentioning
confidence: 99%